Investigating the Impacts of Shame-Proneness on Students' State Shame, Self-Regulation, and Learning - Jeremiah Sullins; Jeannine Turner; Juhee Kim; Steven Barber (MDPI AG, 2024)
We explored relationships between students' shame-proneness and their experiences of state shame, self-regulation, and learning in a laboratory. We conducted two studies with different content: physics (Study 1, n = 179) and the circulatory system (Study 2, n = 85). We first evaluated students' shame-proneness, self-regulation, and content knowledge (pretest). Then, half of the students participated in the experimental condition where state shame was induced. Subsequently, we evaluated students' state shame and learning gains. In both studies, t-tests demonstrated that the experimental manipulation effectively induced higher levels of state shame. Follow-up 2 (experimental/control condition) by 2 (high/low shame-proneness) ANOVAs revealed that, in the experimental shame-induced condition, participants who had high shame-proneness had significantly higher state shame levels than those with low shame-proneness. Regarding students' self-regulation, in both studies, high-shame-prone students had lower self-regulation skills. Interestingly, the outcomes of students' learning gains differed in Studies 1 and 2. The results of a 2 (condition) by 2 (shame-proneness) ANOVA for Study 1 indicated no significant differences in students' learning gains. In Study 2, participants in the experimental condition who reported high shame-proneness had significantly lower learning gains than those with low shame-proneness. We discuss several educational implications and provide directions for future research.